Effect of therapist's active presence on EMG biofeedback training of headache patients - Borgeat, F; Hade, B; Larouche, L M; Bedwani, C N (Biofeedback and self-regulation, 1980)
Sixteen patients suffering from tension or mixed headaches participated in a frontalis EMG treatment schedule of 15 sessions where the therapist was either activity present or almost completely absent. The aim of this study was to evaluate the impact of the therapist's active presence on the subject's ability to lower the EMG level. The active presence of the therapist consistently led to higher frontalis EMG level than that during the therapist's absence. Data also show that the EMG feedback administered was apparently effective in reducing subjective headache intensity along with EMG levels. The findings raise the question of an optimal dosage of presence and activity of the therapist during EMG feedback training.